O JUÍZO DE ADMISSIBILIDADE DO AGRAVO INTERNO NO CÓDIGO DE PROCESSO CIVIL DE 2015 - Domingues, Emmanuel (2020)
This dissertation aims to analyze the admissibility requirements in the Civil Procedure Code of 2015 under the light of the fundamental rules of civil procedure, both constitutional and those inserted in the current procedural codification, standing out t